The impact of intercultural exchange in foreign language learning: a case study in the modern languages program at a University of Quindio (2018)
In this project are contained some important aspects that were studied in order to evaluate the different perspectives of concepts such as culture, language, intercultural competence and bilingualism. They were analyzed thanks to the contributions of recognized authors. Those approaches are fundamental in the study because they allow to go beyond and understand why they have to be involved at the time of learning a second language. The objective of this research is to identify how eight students perceive the implementation of culture in a foreign language learning process. In this respect, it was analyzed how the influence of an intercultural exchange is in the second language learners. Also, it was studied the linguistic and cultural impact on those students who have traveled abroad and to compared with those who had not. On the other hand, another factor that was taken into account in this project was to examine the role of the institution as a resource or a support to those students who want to have an intercultural experience.